2011
DOI: 10.1017/s0144686x11001061
|View full text |Cite
|
Sign up to set email alerts
|

‘The calendar is just about up’: older adults with multiple chronic conditions reflect on death and dying

Abstract: Drawing on data from in-depth interviews with 35 men and women aged 73-91, this article examines the ways in which older adults with multiple chronic conditions talk about and prepare for death and dying. While the focus of the original study did not include questions concerning the end-of-life, the majority of our participants made unprompted remarks regarding their own and others' mortality. The participants discussed the prevalence of death in their lives as it related to the passing of significant others, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 27 publications
2
32
0
2
Order By: Relevance
“…In studies from Taiwan (Ku, Tsai, Lin, & Lin, 2009 ; Lee, Tsai, Chen, & Huang, 2014 ), the Netherlands (Rurup et al., 2011 ) and Sweden (Van Orden et al., 2014 ), older adults with a history of suicidal ideation or behaviour were interviewed about the reasons for their suicidality, while in a Canadian study (Clarke, Korotchenko, & Bundon, 2012 ), older adults were interviewed about preparing for death. Finally, a study from Norway (Kjølseth, Ekeberg, & Steihaug, 2010 ) used a psychological autopsy method to understand the suicide motives of a sample of older adults, from the point of view of their surviving significant others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies from Taiwan (Ku, Tsai, Lin, & Lin, 2009 ; Lee, Tsai, Chen, & Huang, 2014 ), the Netherlands (Rurup et al., 2011 ) and Sweden (Van Orden et al., 2014 ), older adults with a history of suicidal ideation or behaviour were interviewed about the reasons for their suicidality, while in a Canadian study (Clarke, Korotchenko, & Bundon, 2012 ), older adults were interviewed about preparing for death. Finally, a study from Norway (Kjølseth, Ekeberg, & Steihaug, 2010 ) used a psychological autopsy method to understand the suicide motives of a sample of older adults, from the point of view of their surviving significant others.…”
Section: Resultsmentioning
confidence: 99%
“…The Canadian study (Clarke et al., 2012 ) focused on the end of life plans of 19 women and 16 men who had at least three chronic health problems. These respondents, who were between the ages of 73 and 91 and mostly of European descent, were not interviewed about suicide, but the topic of suicide came up.…”
Section: Resultsmentioning
confidence: 99%
“…Some examples include the transitions from adolescence to adulthood, unmarried to married, or employed to retired, as well as promotion within one's career (Kellehear 1990). Status passage has been widely used in the literature in the context of understanding chronic illnesses (Clarke et al 2012;Gibson et al 2017; Kristiansen and Antoft 2016). Glaser and Strauss (1971) identified that status passages were most often scheduled, regularised, and prescribed.…”
Section: Status Passagementioning
confidence: 99%
“…Journal of Current Cultural Research techniques of modern medicine provide a sense that death is controllable and subject to timing, when, for example, people in their nineties estimate healthy life years left to them in relation to the possibility of complex treatments and surgeries (Kaufman 2010;Clarke 2012). But when timing and control become important characteristics of the good death, the idea of the natural death becomes even more paradoxical.…”
Section: Culture Unboundmentioning
confidence: 99%
“…As Clarke et al argue, research on the experience of living in a dying body has received only scant attention in gerontological studies (Clarke et al 2012). In general, the focus in these studies is on successful ageing, which overshadows living experiences that are somewhat incompatible with the notion of successful ageing (Bülow 2014).…”
Section: Culture Unboundmentioning
confidence: 99%